Adherent junctions: Physiology, role in hydrocephalus and potential therapeutic targets - Zhiye Chen; Jian He; Yating Guo; Yue Hao; Wentao Lv; Zexin Chen; Junqiang Wang; Yijian Yang; Kaiyue Wang; Zhikun Liu; Qian Ouyang; Zhangjie Su; et al. (IBRO Neuroscience Reports)
In all epithelial cells, the adherent junctions (AJs) with cadherin as the core play an important role in the maintenance of the connection and the formation of apical-basal polarity. The ependymal cells close to the ventricular system rely on AJs with N-cadherin at the core to maintain their normal morphology and function. Therefore, it has an important impact on the function and disease of the central nervous system. Hydrocephalus is a pathological phenomenon of excessive cerebrospinal fluid accumulating in the ventricular system accompanied by continuous ventricular dilatation, which can be divided into obstructive hydrocephalus and communicating hydrocephalus according to the pathogenesis. Obstructive hydrocephalus is often associated with excessive ependymal cells produced by differentiation of radial glial cells. The etiology of communicating hydrocephalus is mainly related to the dyskinesia of cerebrospinal fluid. In addition, the damage of the brain barrier can lead to brain edema and aggravate the symptoms. At present, the researches on the pathogenesis of hydrocephalus are mainly focused on the development of ependymal cells and cilia, while less attention has been paid to molecules such as AJs, which play an important role in maintaining the polarity of ependymal cells. This paper discusses the formation and function of AJs and their role in preventing hydrocephalus by preserving the polarity of ependymal cilia, regulating the number of ependymal cells, and upholding the brain barrier integrity to impede hydrocephalus exacerbation, which provides a new direction for the study of hydrocephalus.